Structure and electrochemical hydrogen storage characteristics of Ce-Mg-Ni-based alloys synthesized by mechanical milling - 张羊换 冯佃臣 孙昊 卜文刚 祁焱 郭世海 (Journal of rare earths, 2017)
The substituting Mg with Ni and milling as-cast alloy with Ni were adopted to obtain nanocrystalline/amorphous CeMgnNi＋x wt.%Ni（x=100,200） alloys and promote the electrochemical hydrogen storage performances of CeMg_（12）-type alloys.Analyzing the structural features of the alloys provided a mechanism for ameliorating the electrochemical hydrogen storage properties.The electrochemical tests demonstrated that all the alloys just needed one cycle to be activated.Rising Ni proportion had an obvious role on charge-discharge reaction.The discharge capacities of the as-milled（60 h） alloys increased sharply from 182.0 mAh/gfor x=100 alloy to 1010.2 mAh/gfor x=200 alloy at current density of 60 mAh/g.Furthermore,milling time largely determined the performances of electrochemical reaction.The discharge capacity continued to grow along with prolonging milling time,while the cycle stability obviously decreased for x=100 alloy,and first declined and then augmented for the x=200 alloy with milling time extending.In addition,there was an optimal value with milling time varying for the high rate discharge abilities（HRD）,which was 80.3%for x=100 alloys and 86.73%for x=200,respectively.